Effectiveness of Wharton's jelly stem cells in gastroschisis repair using the inner surface of the umbilical cord as a patch: long-term results. Issue 3 (July 2015) - Zivkovic, Stojan M.; Djordjevic, Miroslav; Milic, Natasa; Smoljanic, Zeljko; Djuricic, Goran; Pavicevic, Polina; Keserovic, Branislava; Stojanovic, Borko
Abstract : Objective: This retrospective study was designed to assess and compare the anatomical, functional, and esthetic appearance of the umbilical area in patients after repair of gastroschisis using the inner surface of the umbilical cord (UC) and in patients with omphalocele conservatively treated. Background: Our procedure transformed gastroschisis into an 'artificial–surgical omphalocele' in which the prolapsed intestine was covered with an umbilical patch, the inner surface of which contained Wharton's jelly (WJ). Methods: We have summarized an experience of 17 years in repairing gastroschisis using the inner surface of the UC. From 1986 to 2003, 21 infants with gastroschisis and one with a ruptured omphalocele were treated with this technique. We used Eagle's medium to prove the validity of the umbilical stump and the duration of its viability. The inner surface of the umbilical patch is a 'live' structure with WJ, which contains mucoid connective tissue and fibroblast-like cells – that is, stem cells producing cutis, adipose, and connective tissue. Results: Using our method, early control assessment of 18 of 21 patients with gastroschisis, at intervals of 1–3 months, showed good functional and esthetic results. Clinical long-term results in terms of anatomical, clinical, and functional findings were excellent. Besides clinical testimony, we used high-frequency ultrasonography to make an appraisal of the effectiveness of WJ stem cells in the repair of gastroschisis, and compared our results with healthy volunteers and patients with omphalocele conservatively treated. Conclusion: This paper describes the effect of the local application of WJ – that is, mesenchymal stromal cells derived from the inner surface of the umbilical stump – and its influence on the healing process of the birth defect and wound.